Comparative Analysis Of Consumer Preferences In Online Food Delivery Services: Gofood And Shopeefood In Pekanbaru City - Ayu Sefhia; Jushermi Jushermi; Agnes Alvionita (West Science Business and Management, 2026)
The growth of the Online Food Delivery (OFD) industry requires service providers to continuously innovate. This research focuses on comparing consumer preferences between GoFood and ShopeeFood in a developing city like Pekanbaru, to fill the gap of previous studies that generally compared GoFood and GrabFood in metropolitan cities. This study aims to determine the differences in consumer preferences towards GoFood and ShopeeFood services in Pekanbaru City based on the aspects of service quality, discounts, prices, restaurant partners, and application user experience. This study uses a quantitative approach. The population includes all consumers who use GoFood and ShopeeFood in Pekanbaru City. The sampling was conducted using a non-probability sampling method with a purposive sampling technique, determining 100 respondents based on specific criteria. The data analysis method used is a comparative analysis with a difference test technique (Paired Sample T-Test) processed using IBM SPSS Statistics software. The results conclude that there are significant differences in consumer preferences between GoFood and ShopeeFood. Specifically, the ShopeeFood platform is more dominantly considered by consumers regarding discount and price factors, while the GoFood platform shows superiority in service quality, diversity of restaurant partners, and application user experience.